Sleep and theology: ‘An half adieu to the world’ - Bishop, Andrew (International journal for the study of the Christian church, 2017)
The study of sleep has become a field of widespread interest. It engages many disciplines from neuroscience to sociology, philosophy to evolutionary biology. It features in the lifestyle sections of newspapers and websites often because of its connections with mental and physical wellbeing. Yet theology has, in the most part, remained silent on the subject, despite many Biblical references to sleep in both the Old and New Testaments. There is a theological story to be told about sleep − as a gift, and not an affliction − despite the unfortunate occasional conflation of sleep with sloth. It is a state of grace and not of sin. It refreshes and renews yet can never be earned; all we can do is to be in a posture of receptivity so that it falls upon us. Sleep is profoundly precarious and sometimes frustratingly elusive and is suggestive of the fragility and vulnerability of human existence. When it comes to us, sleep transforms our experience of waking life. The eschatological character of sleep points us to reflect on mortality and resurrection. This article argues that it is possible to speak of a ‘theology of sleep’, but that it is not to be found in a coherent body of teaching or theological exploration. Rather, a theology of sleep is found articulated in Christian practices such as the Office of Compline, the keeping of vigils and the Examen of Consciousness, and in evening hymnody and prayers before bed. The author will suggest that the word theosomnia encapsulates this understanding of sleep.